Training Management in Improving Teacher Performance - Ahmad Rusyadi; Abin Syamsudin; Iim Wasliman; Mustatul Anwar (International Journal of Nusantara Islam, 2019)
The title of this thesis is "Management Education And Training To Improve Teacher Professionalism" (Descriptive Analysis Study in MAN 2 HSU, MAN 3 HSU in Kabupaten Hulu Sungai Utara). Problems that occur in education and training include education and training have not been done in a sustainable manner, the implementation of education and training has not been well scheduled, the implementation of education and training is very short, the implementation of education and training are partial and the development of overlapping material spends much time so inefficient, the competence of speakers is still lacking in education and training, and the time of education and training disrupt the process of teaching and learning activities take place. The purpose of this research is to know the planning, organizing, implementation, supervision, and effort to overcome inhibiting factor of education and training at MAN 2 HSU, MAN 3 HSU. This research is a qualitative research with descriptive method, because this study aims to get a deep picture. Data collection techniques used are observation, interview, and documentation. The main instruments are observation guides, interview guides, and documentation. Data were analyzed using data reduction, data presentation, and conclusions. Technique of examination of data validity by triangulation of source and technique. The results of this study indicate that the planning of education and training begins with the determination of needs as a first step in making the planning, organizing in the provision of education and training has been done based on the stages of implementation both theoretical, technical, and resources, evaluation of education and training conducted with 3 (three) stages of activities consisting of pre-training stage, stage during training and post-training stage, and efforts to overcome inhibiting factors of education and training not only from the implementers but from all elements in the provision of education and training including education and training participants . So based on the results of research that 2 schools have not reached the level of professionalism of teachers.